(untitled) (Global Journal of Science Frontier Research, 2024)
In this paper the mathematical analysis is carried out from many angles so that the theoretical calculation problem of the circular metal wall cut-off waveguide used as a premary attenuation standard is completely solved and the Chinese national standard of the attenuation quantity is established The benchmark was completed by the Chinese National Institute of Metrology NIM with an accuracy of 5 10-5 Reach the international advanced level The calculation accuracy provided in this paper is 10-6 10-7 This is a good example of a project combining theory and practice There are a series of original achievements in this paper 1 a new method for solving CMS equation accurately is proposed 2 The precise attenuation constant formula is derived by the surface impedance perturbation method that is the formula later called the Huang s equation is proposed 3 The general theory of metal-walled circular waveguides lined with dielectric layers namely the Huang Zen equation is presented 4 The influence of oxide layer on the inner surface of the circular waveguide is analyzed and calculated The calculation results of HE11 mode of circular cut-off waveguide are obtained Therefore the basic mathematical physics equations are also contributed